Application of calcium oxide as heterogeneous catalyst for ethylic transesterification of residual frying soybean oil - Lenz, Djonathan Luiz Giordani; Guimarães, Pedro Vinnicius Caitano; Cabrera, Liziara da Costa; Dugatto, Jonas Simon; Wenzel, Bruno München (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
Biodiesel can be produced through the transesterification reaction of a short-chain alcohol with a triacylglycerol, that can be obtained from vegetable oils or animal fats, in the presence of a catalyst. The use of ethanol as reactant is justified since its production is consolidated in Brazil. Among the heterogeneous catalysts, CaO shows potential in the transesterification reactions because it has a low cost, can be reused and is not corrosive. The recycling of frying oil for the production of biodiesel represents an alternative for the disposal of a waste and does not compete with the food industry. The residual oil and CaO were subjected to a pre-treatment before the transesterification reactions. A Box-Behnken experimental design was applied with 3 factors: temperature, ethanol:oil molar ratio and reaction time. The reactions were carried out in a batch reactor, in which oil, ethanol and the catalyst were added. The samples were vacuum filtered and conducted to a rotary evaporator, in order to remove excess ethanol. The resulting mixture was centrifuged and, subsequently, a sample was collected from the supernatant phase. The yield was determined by a mass balance based in the concentrations of acylglycerols, that were determined through an HPLC-UV methodology. A second-order linear regression model was built and validated through statistic tests with a 5% significance level. The optimized operational parameters are 15:1 ethanol:oil molar ratio, 81.2 ºC e 6 h of reaction. From the obtained results it can be inferred that it is feasible to use residual frying oil as raw material, ethanol as reactant and CaO as catalyst for the production of biodiesel.